Coatings and surface treatments for enhanced performance suspensions for future gravitational wave detectors. (15th November 2017) - Birney, R; Cumming, A V; Campsie, P; Gibson, D; Hammond, G D; Hough, J; Martin, I W; Reid, S; Rowan, S; Song, S; Talbot, C; Vine, D; et al.
Abstract: Further improvements in the low frequency sensitivity of gravitational wave detectors are important for increasing the observable population of astrophysical sources, such as intermediate mass compact black hole binary systems. Improvements in the lower stage mirror and suspension systems will set challenging targets for the required thermal noise performance of the cantilever blade springs, which provide vertical softness and, thus, isolation to the mirror suspension stack. This is required due to the coupling between the vertical and horizontal axes due to the curvature of the Earth. This can be achieved through use of high mechanical Q materials, which are compatible with cryogenic cooling, such as crystalline silicon. However, such materials are brittle, posing further challenges for assembly/jointing and, more generally, for long-term robustness. Here, we report on experimental studies of the breaking strength of silicon at room temperature, via both tensile and 4-point flexural testing; and on the effects of various surface treatments and coatings on durability and strength. Single- and multi-layer DLC (diamond-like carbon) coatings, together with magnetron-sputtered silica and thermally-grown silica, are investigated, as are the effects of substrate preparation and argon plasma pre-treatment. Application of single- or multi-layer DLC coatings can significantly improve the failure stress of silicon flexures, in addition to improved robustness for handling (assessed through abrasion tests). Improvements of up to 80% in tensile strength, a twofold increase in flexural strength, in addition to a 6.4 times reduction in the vertical thermal noise contribution of the suspension stack at 10 Hz are reported (compared to current Advanced LIGO design). The use of silicon blade springs would also significantly reduce potential 'crackling noise' associated with the underlying discrete events associated with plastic deformation in loaded flexures.